Let's check every way:
* Multiply 4p + 2q = 62 by 2, then subtract 8p - q = 59 from the result:
![\begin{gathered} 2\cdot(4p+2q)=62\cdot2 \\ 8p+4q=124 \\ 8p+4q-(8p-q)=124-59 \\ 5q=65 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/tyv5zo4m2gi0870s4ul6ns3wr44n61l9sf.png)
The first way works really well since we are able to eliminate one of the variables and get one equation and one unknown, which is very simple to solve.
-------------------------------
Multiply 8p - q = 59 by 2, then add the result to 4p + 2q = 62:
![\begin{gathered} 2\cdot(8p-q)=59\cdot2 \\ 16p-2q=118 \\ 16p-2q+(4p+2q)=118+62 \\ 20p=180 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/98n3466vzjfia4vh05zneglirdhql4d99n.png)
The second way is also a valid option since we were able to eliminate one of the variables ang get a equation with one unknown.
------------------------------------------
Both methods work really well, in the first method we eliminated the variable p and in the second method we eliminated the variable q.